2002
DOI: 10.1542/peds.110.6.e70
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Arousals in Supine Infants While Swaddled and Unswaddled During Rapid Eye Movement and Quiet Sleep

Abstract: ABSTRACT. Objective. Supine sleep is recommended for infants to decrease the risk of sudden infant death syndrome, but many parents report that their infants seem uncomfortable supine. Many cultures swaddle infants for sleep in the supine position. Swaddled infants are said to "sleep better"; presumably they sleep longer or with fewer arousals. However, there have been no studies of the effect of swaddling on spontaneous arousals during sleep. Arousal is initiated in brainstem centers and manifests as a sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
1
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 23 publications
2
35
1
6
Order By: Relevance
“…32 Even more interesting is the finding that swaddling enhances the incidence of REM sleep in infants and has an inhibitory effect on spontaneous arousals during sleep (Gerard et al 2002;Franco et al 2005). 33 These findings are well in line with postulates of the present hypothesis.…”
Section: Childrearing Practices and Immobilizationsupporting
confidence: 56%
“…32 Even more interesting is the finding that swaddling enhances the incidence of REM sleep in infants and has an inhibitory effect on spontaneous arousals during sleep (Gerard et al 2002;Franco et al 2005). 33 These findings are well in line with postulates of the present hypothesis.…”
Section: Childrearing Practices and Immobilizationsupporting
confidence: 56%
“…It has been reported that swaddling infants for sleep is gaining popularity in countries such as the United Kingdom and the United States, [1][2][3] with several reported benefits to the practice. For the general population of young infants, these include more quiet sleep, 3 fewer spontaneous arousals during quiet sleep, 4 and a slight reduction in excessive crying in infants aged <7 weeks. 5 Further benefits are observed for specific populations, including improvements in neuromuscular development for very low birth weight infants, 6 reduced physiologic and behavioral distress among premature infants, 7 and improved calming and sleep for infants with neonatal abstinence syndrome.…”
mentioning
confidence: 99%
“…11 In contrast, there is evidence that swaddling may increase the risk of SIDS, as swaddled infants have fewer spontaneous arousals from sleep and increased sleep time, particularly during quiet sleep, which is a state of reduced arousability. 4 In addition, those infants who were naive to swaddling (ie, not routinely swaddled) had higher induced arousal thresholds in both sleep states 2 and reduced spontaneous arousability in active sleep. 12 Beyond the field of SIDS, swaddling may also increase an infant's risk for developmental dysplasia of the hip (especially if not applied well), 13 hyperthermia, 1 pneumonia, and upper respiratory tract infections.…”
mentioning
confidence: 99%
“…Third, it facilitates the development of sensorimotor experiences and promotes neuronal maturation since infants interact with their environment through their own activities. Positioning has been employed in developmental care [23][24][25] using the swaddling and nesting technique, and there are some studies reporting the effects of these techniques [26][27][28][29][30] . However, most of the research has focused on developmental care as a whole and little is known about the effect of the positioning technique on the movement patterns of very lowbirth-weight infants.…”
Section: Discussionmentioning
confidence: 99%